Automatic morpheme identification across development: Magnetoencephalography (MEG) evidence from fast periodic visual stimulation - Pescuma, Valentina N.; Ktori, Maria; Beyersmann, Elisabeth; Sowman, Paul F.; Castles, Anne; Crepaldi, Davide (Frontiers in Psychology, 2022)
The present study combined magnetoencephalography (MEG) recordings with fast periodic visual stimulation (FPVS) to investigate automatic neural responses to morphemes in developing and skilled readers. Native English-speaking children (N=17, grade 5-6) and adults (N=28) were presented with rapid streams of base stimuli (stimulation frequency: 6 Hz) interleaved periodically with oddballs (stimulation frequency: 1.2 Hz). A manipulation-check condition, tapping into whole word recognition, featured words embedded in consonant strings. In the experimental conditions, the contrast between oddball and base stimuli was manipulated in order to probe selective stem and suffix identification in morphologically structured pseudowords. As expected, sensor-level cluster-based permutation analyses revealed a significant cluster at the oddball frequency and its harmonics in the word condition (e.g., roll in kltq). As for the experimental conditions, a significant cluster emerged for adult readers in centrally-located and left-lateralized occipital sensors, in the condition tracking suffix identification in the presence of stems (e.g., softity in terpert). In developing readers, a significant occipital cluster, mostly located around the midline, emerged in the condition which tracked stem identification in the presence of suffixes, with oddballs entirely made of morphemes (e.g., softity in terpity). The present findings suggest that sensitivity to morphological structure, in the absence of explicit meaning assignment, has matured by fifth-sixth grade. Moreover, morpheme identification appears to be modulated by the context in which morphemes are presented, as an oddball response only emerged for pseudowords that could be exhaustively decomposed into stems and suffixes. Such response is compatible with a source in the ventral occipito-temporal cortex, in line with accounts of (early) morphological identification as predominantly visual. However, a response also emerged in sensors that might capture activity in areas responsible for deeper processing, perhaps up to the semantic level.